(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study was designed to study the Hematology and Serum biochemistry of Broiler Chickens Fed Red Sorghum (Sorghum bicolor (L.) Moench) Based Diets supplemented with Complex Enzyme (Kingzyme®). Two hundred (200) chicks (day-old) of mixed sex was randomly allotted to five dietary treatments (T1, T2, T3, T4 and T5) supplemented with enzyme complex (Kingzyme®) at the levels of 0.0g, 0.2g, 0.5g, 0.8g and 1.1g kg per Kg of feed respectively in a Completely Randomized Design (CRD). Each treatment was replicated four (4) times to contain ten (10) birds each. Feed and water were provided ad libitum accompanied with standard management procedures for eight weeks. At end of the eight weeks’ experimental period, blood samples were collected for hematological and serum chemistry analysis. Data were analyzed using Statitix Analytical Software, Version 10; and the treatment means were compared using Turkey HSD.Except the RBC, MCV, MCH and Eosinophil which showed significant (P < 0.05) difference across the treatment groups, all other hematological parameters were not significantly (P > 0.05) affected. The TP, Alb and Glb were also not significantly (P > 0.05) affected. The Urea and Glucose were not significantly (P > 0.05) affected. The Creatinine and Cholesterol were significantly (P > 0.05) affected across the dietary treatment. Based on the result of the study, it was concluded that Red Sorghum-based diet supplemented with enzyme complex (Kingzyme®) do not have any significant effect on hematological and serum biochemistry of broiler chickens.